The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10086-015-1500-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing sawing of boards for furniture production using CT log scanning

Abstract: The inherent variability of wood material together with sub-optimization in production processes means that a lot of potential value is lost. Computed tomography scanning together with simulation models of the production processes could remedy this, and ensure optimization of the entire production process. Therefore, the purpose of this study was to investigate if such methods can be used to optimize the sawing position of logs in a production process including further processing, in this case crosscutting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The measurement of leakage radiation during scanning was performed with a metrologically verified instrument. The measured value was the ambient dose equivalent rate 𝐻𝐻 ̇ * (10). The measurement was carried out on 7th of October 2022.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of leakage radiation during scanning was performed with a metrologically verified instrument. The measured value was the ambient dose equivalent rate 𝐻𝐻 ̇ * (10). The measurement was carried out on 7th of October 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The measured value was the ambient dose equivalent rate . H * (10). The measurement was carried out on 7th of October 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to algorithms for knot detection [294][295][296], algorithms developed include pith detection [297], fiber orientation [298], spiral grain [299], decay recognition [300], and moisture distribution mapping [301]. Ultimately mapping internal log defects prior to sawing allows for improved lumber value recovery during processing [302][303][304]. Studies have also examined variation within and among stems, e.g., [305], verified light detection and ranging (LiDAR) measurements of wood quality assessment with verification by X-ray CT data [306], and prediction of stiffness of sawn products based on log scans [307].…”
Section: Computer Tomography (Ct) Scanningmentioning
confidence: 99%
“…For the wood industry, several studies [1][2] [3] showed that the transformation of the wood based on the internal density of the log improved the value recovery. Knots are considered as the main important inner element of the wood.…”
Section: Introductionmentioning
confidence: 99%